Laser-Induced Thermal Treatment of Superficial Human Tumors: An Advanced Heating Strategy and Non-Arrhenius Law for Living Tissues - Dombrovsky, Leonid A. (Frontiers in Thermal Engineering, 2022)
The most interesting, but insufficiently known results obtained by the author in modeling laser-induced hyperthermia of human tumors are discussed. It is important that the traditional equation for the local bio-heat transfer does not work in superficial layers of the body. It is shown also that the classical Arrhenius law is not applicable to living tissues because of the tissue regeneration due to oxygen supplied by the arterial blood. The latter is one of the main reasons of the suggested strategy of laser heating of tumors in the therapeutic window of semitransparency when the tumor asphyxiation is considered as one of important weapons against the cancer. The other advantages of this advanced strategy of a soft thermal treatment (in few of sessions), which is painless for patients, are discussed as well. Some features of modeling various heat transfer modes are also considered. The best choice between the simplest differential models for the radiative transfer calculations is dependent of the particular problem statement. The known finite-difference or finite element algorithms can be preferable in solving transient heat transfer problems. As a rule, it depends on the shape of the computational region. It is expected that this paper will help the colleagues to overcome some typical weaknesses of computational modeling of infrared photothermal treatment of superficial tumors.